1994
DOI: 10.1006/exnr.1994.1188
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Inhibits Purkinje Cell Survival and Dendritic Differentiation in Organotypic Cultures of the Mouse Cerebellum

Abstract: The effects of morphine on the morphogenesis and survival of calbindin-D 28k immunoreactive Purkinje cells was studied in organotypic explant cultures isolated from 1-or 7-day-old mouse cerebella. To reduce experimental variability, bilaterally matched pairs of organotypic cultures were used to compare the effects of opiate drug treatment. One explant within each pair was untreated, while the remaining explant was continuously treated for 7 to 10 days with morphine, morphine plus naloxone, or naloxone alone. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 63 publications
2
49
0
Order By: Relevance
“…Morphine sulfate administration can also cause neurotoxic effects on the cerebellar and cerebral cortex by reducing both cortical thickness and the number of neurons in the developing fetal central nervous system (SADRAIE et al, 2008), also significantly reducing the Purkinje cell count (BEKHEET et al, 2010). Purkinje cells in morphine treated animals might be lost by apoptosis and/or necrosis (HAUSER et al, 1994). The morphometric results of the present study showed that morphine-treatment significantly decreased the Purkinje cell count in a unit length of the ganglionic layer in both genders in a similar manner.…”
Section: Methodssupporting
confidence: 68%
See 2 more Smart Citations
“…Morphine sulfate administration can also cause neurotoxic effects on the cerebellar and cerebral cortex by reducing both cortical thickness and the number of neurons in the developing fetal central nervous system (SADRAIE et al, 2008), also significantly reducing the Purkinje cell count (BEKHEET et al, 2010). Purkinje cells in morphine treated animals might be lost by apoptosis and/or necrosis (HAUSER et al, 1994). The morphometric results of the present study showed that morphine-treatment significantly decreased the Purkinje cell count in a unit length of the ganglionic layer in both genders in a similar manner.…”
Section: Methodssupporting
confidence: 68%
“…In a later study, HAUSER et al (1994) showed that morphine significantly decreased Purkinje cell survival at higher concentrations, by decreasing the cells' survival. the researchers concluded that morphine can affect Purkinje cell differentiation and survival, and there is a critical period during development when Purkinje cells are especially vulnerable to the effects of morphine.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, some of the diversity of opioid actions in part results from an apparent promiscuity in coupling between individual opioid receptor types and particular G-protein coupled-intracellular effector pathways (16,34,37,90). In the cerebellum, rather than being neuroprotective, high concentrations of morphine are neurotoxic to Purkinje cells through an action at μ opioid receptors (33). Lastly, any potentially neuroprotective effects of κ receptor activation appear to be offset by the more deleterious systemic pathophysiological actions of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic pruning and selective postsynaptic damage have been reported with HIV-1 or SIV infections in the CNS. 46 -48 In addition to viral and cellular toxins associated with HIV, 2,49,50 endogenous opioids, 32,51 as well as opioid drugs such as morphine and methadone, [52][53][54] can also shrink dendrites and reduce the density of their spines. 43,55 Opioid drugs also affect the plasticity of adult neurons.…”
Section: Structural Changes In Dendrites Induced By Hiv-1 Tat ϯ Morphinementioning
confidence: 99%